PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN PADA SEKTOR KEUANGAN YANG TERCATAT DI BURSA EFEK INDONESIA PADA TAHUN 2007-2010 - Hastuti, Rini Tri; Suhendah, Rousilita (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
This research examine the effect of insider ownership and institutional ownership on corporate performance on financial sector that listed in Indonesia Stock Exchange on 2007-2010.There is 11th banking on this sample with multiple purposive sampling criteria. Research data was collected from Indonesian Capital Market Diectory. This research findings are insider ownership significant effected operational expenses to operational income ratio and Loan to deposit ratio. But this failed to examine that institusional ownership effect operational expenses to operational income ratio and Loan to deposit ratio. The result of this study revealed that insider ownership and institusional ownership did not affect leverage.